TEX-SIS FOLLOW-UP Student Follow-up Management Information System. Procedures Manual. - Tarrant County Junior Coll. District, Ft. Worth, TX.; Tarrant County Junior Coll. District, Ft. Worth, TX. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
Project FOLLOW-UP was conducted to develop, test, and validate a statewide management information system for follow-up of Texas public junior and community college students. The results of this project was a student information system (TEX-SIS) consisting of seven subsystems: (1) Student's Educational Intent, (2) Nonreturning Student Follow-up, (3) Withdrawal Follow-up, (4) Graduate Follow-up, (5) Employer Follow-up, (6) Adult and Continuing Education Follow-up, and (7) State Follow-up Reporting. The bulk of this manual is comprised of sections for each subsystem of SIS, describing in detail the type of information collected by each SIS instrument, procedures for data collection, preparation and special coding of data, processing the data, report format and reporting, and survey evaluation. Sample survey evaluation and reporting forms are included. A final section makes suggestions concerning an appropriate schedule for implementation of the seven types of follow-up studies over a 10 year cycle. This manual is intended for use in conjunction with the TEX-SIS FOLLOW-UP Activities Manual (JC 760 474) and Data Processing Manual (JC 760 476). (JDS)
Sponsoring Agency: Texas Education Agency, Austin. Div. of Occupational Research and Development.
ERIC Note: For related documents, see JC 760 473-483; For a previous project study see ED 118 164.
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Colleges; Data Collection; Educational Assessment; Followup Studies; Guides; Institutional Research; Management Information Systems; Questionnaires; Research Methodology; State Programs; Two Year Colleges; Project FOLLOW UP; Student Followup Management Information System -- TEX SIS FOLLOW UP -- Texas; Guides, General